Human Motion Tracking And Analysis Via Point Tracking Technique. - Arshad, Mohd Rizal; Nordin, Nadira (2007)
The main objective of this paper is to present a two-dimensional vision system for human gait motion analysis and provides pertinent information on human walking parameters.